(untitled) (International Nexus Multidisciplinary Research Journal, 2025)
Education financing remains a critical driver of national development; however, in Nigeria, increased funding has not translated into proportional improvements in learning outcomes, reflecting a persistent policy paradox. This study examined the structural, institutional and equity-related challenges that undermine the effectiveness of education financing in Nigeria’s public education system. Despite rising budgetary allocations, inefficiencies such as poor resource allocation, corruption, weak governance and limited management capacity continue to impede the optimal utilization of funds. Furthermore, disparities in the distribution of educational resources perpetuate inequality, as rural schools, girls and learners with disabilities remain underfunded and underserved. These systemic and equity constraints revealed that the mere expansion of financial inputs is insufficient to achieve quality education and equitable outcomes. The study emphasized the need for a paradigm shift from input-based to outcome-based financing models that link expenditure to measurable learning results. It recommended strengthening governance through transparent budget monitoring, building institutional and leadership capacity in financial management and strategic planning, and implementing needs-based funding formulas to promote inclusivity. Additionally, robust monitoring and evaluation frameworks and multi-stakeholder partnerships are proposed to enhance accountability and ensure that investments yield tangible educational improvements.